2020
DOI: 10.3390/molecules25204652
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Perspectives of Adenosine Deaminase Inhibition in Cardiovascular Diseases

Abstract: Adenosine deaminase (ADA) is an enzyme of purine metabolism that irreversibly converts adenosine to inosine or 2′deoxyadenosine to 2′deoxyinosine. ADA is active both inside the cell and on the cell surface where it was found to interact with membrane proteins, such as CD26 and adenosine receptors, forming ecto-ADA (eADA). In addition to adenosine uptake, the activity of eADA is an essential mechanism that terminates adenosine signaling. This is particularly important in cardiovascular system, where adenosine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 164 publications
1
39
1
1
Order By: Relevance
“…Growing evidences have shown that inhibition of ADA is beneficial for ameliorating some diseases. Pentostatin is a potent ADA inhibitor that, when applied to atherosclerotic mice, exerted anti-atherosclerotic effects by reducing macrophage accumulation and improving endothelial function ( 29 ). In hyperthyroidism pig, the administration of pentostatin significantly increased adenosine levels, enhanced A1 adenosinergic system, which in turn exerted negative inotropic effects and might ultimately improve myocardial ischemia ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences have shown that inhibition of ADA is beneficial for ameliorating some diseases. Pentostatin is a potent ADA inhibitor that, when applied to atherosclerotic mice, exerted anti-atherosclerotic effects by reducing macrophage accumulation and improving endothelial function ( 29 ). In hyperthyroidism pig, the administration of pentostatin significantly increased adenosine levels, enhanced A1 adenosinergic system, which in turn exerted negative inotropic effects and might ultimately improve myocardial ischemia ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that extracellular adenosine pool depletion is an important factor in the development of cardiovascular pathologies. Recently, we highlighted the therapeutic perspectives of eADA inhibition in the treatment of cardiovascular diseases such as atherosclerosis, myocardial ischemia-reperfusion injury, or hypertension [ 123 ]. Moreover, a study underlined that intrastriatal administration of ecto-nucleoside transporter (ENT) inhibitors increased the extracellular level of adenosine in the striatum of R6/2 mice to a much higher level, compared to controls, and improved HD mouse survival [ 124 ].…”
Section: Purine Nucleotides Metabolism and Signaling As A Target For Huntington’s Disease Therapiesmentioning
confidence: 99%
“…To understand why the metabolism of ADO is limited, it is important to underline that this nucleoside, once formed in the extracellular environment, is actively regained inside cells by specific (equilibrative and concentrative) transporters [ 49 ]. It is noteworthy that ADO uptake as well as e-ADA activity are essential mechanisms that terminate ADO signaling [ 50 ]. It should also be noted that ADO metabolites such as inosine and hypoxanthine can be taken up into cells by the same carriers mentioned above or by others [ 51 ], which help remove compounds from the extracellular fluid that need to be recovered.…”
Section: Enzymes and Other Mechanisms Generally Involved In The Turnover Of Extracellular Purinesmentioning
confidence: 99%